2000
DOI: 10.1007/bf02903884
|View full text |Cite
|
Sign up to set email alerts
|

Microwave synthesis of electrode materials for lithium batteries

Abstract: Abstract. A novel microwave method is described for the preparation of electrode materials required for lithium batteries. The method is simple, fast and carried out in most cases with the same starting material as in conventional methods. Good crystallinity has been noted and lower temperatures of reaction has been inferred in cases where low temperature products have been identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 43 publications
(28 reference statements)
0
18
0
Order By: Relevance
“…LiCoO 2 has a layered rocksalt structure (4,7) and Li + ions can be deintercalated reversibly to a very high extent (up to 80%) and with good cyclability (8,9). However, it has been noted that LiCoO 2 prepared by different methods exhibits significant differences in its electrode behavior (10)(11)(12). Although electrode materials synthesized at low temperature exhibit better cyclability, the nature of the site occupied by lithium has been found to be altered significantly during cycling, which affects the cell capacity (13).…”
Section: Introductionmentioning
confidence: 99%
“…LiCoO 2 has a layered rocksalt structure (4,7) and Li + ions can be deintercalated reversibly to a very high extent (up to 80%) and with good cyclability (8,9). However, it has been noted that LiCoO 2 prepared by different methods exhibits significant differences in its electrode behavior (10)(11)(12). Although electrode materials synthesized at low temperature exhibit better cyclability, the nature of the site occupied by lithium has been found to be altered significantly during cycling, which affects the cell capacity (13).…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, development of different synthetic techniques such as soft chemical and sol-gel methods have led to the engineering materials (Gopalakrishnan 1995). Now a days microwave assisted synthetic route is becoming a very rapidly developed method (Rao et al 1999a,b;Harish Bhat et al 2000;ChungChen and Huang 2002;Lagashetty et al 2002). New Chimie-Douce routes for the synthesis of cobalt ferrite and other ceramics are being continuously investigated (Figlarz 1989;Lee et al 1998;Helen and Kamath 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that cubic spinel formed directly in a single heating step of 6 min. The authors have also investigated on the effect of starting compounds and their susceptibility in achieving the final crystalline compounds and it has been conceded that at least one of the reactants should have high microwave susceptibility to achieve good crystallinity [38].…”
Section: Limn 2 O 4 and Its Derivativesmentioning
confidence: 99%